PERSONALIDADE, ESTILOS PARENTAIS E COGNIÇÃO EM MENINOS VÍTIMAS DE ABUSO SEXUAL - ABECHE, CAMILA VAZ (2016)
There is a consensus in the literature that the experience of sexual abuse in childhood leads to a series of consequences, both physical and psychological, to the victims. The scenario of violence against children and adolescents is increasing in contemporary society, becoming a public health problem, so the need for a closer look of professional and public policy development for both the prevention of such cases to the treatment of their problems arising. In children, there is an association of increased behavioral and psychological problems which may extend the period until adulthood. Other studies emphasize changes in brain areas and relate to the emergence of mental disorders in the population of child victims of sexual violence, among other types of violence. The aim of this study was to verify the presence of personality traits, developed parenting styles and cognitive performance, specifically executive functions in children with a history of sexual abuse. We evaluated 62 children and adolescents (32 with a history of sexual abuse and 30 without), and the average age abuse group of members is 11.7 years old and their mostly divorced parents, unlike the control group, in which the parents are mostly married. The method consisted of sociodemographic questionnaire, neuropsychological tests assessing executive functions (Wisconsin Card Sortint Test, figures Ray and WISC III - Similarities, Picture Arrangement, Understanding, cubes, digits and Vocabulary), Personality Questionnaire for Children and Adolescents (EPQ-J) and Parental Styles Inventory (IEP). There were no significant results between abuse and executive functions, both in the Wechsler Intelligence Scale for Children - Third Edition (WISC-III) subtests and in Wisconsin; but the group showed significantly lower data in the memory of Complex Figure Rey. Regarding the EPQ-J, the results showed higher levels of neuroticism, which can be associated with symptoms of depression, and had lower rates in extroversion, bringing potential difficulties in social relations. Regarding parenting styles, the group presented difficulties and losses in the perceptions of parents, especially in relation to the parent, which is the biggest abuser statistically. The data showed a correlation between neuroticism and vocabulary, parenting styles and vocabulary, and neuroticism and parenting styles. The importance of further studies with the male audience was observed, so that they can be elucidated more comprehensively the issues of sexual abuse and their interference in the neuropsychological aspects, Parenting Styles and Personality Traits, since most of the studies is related the female audience. The development of public policies for the specific care of the male audience is necessary that suffer abuse, and that the health professional is prepared to help, strengthening the psychological and emotional aspects